Old-growth and secondary Araucaria Forest characterization - Douglas Rufino Vaz; Mário Dobner, Jr.; Marcelo Callegari Scipioni; Marcos Felipe Nicoletti; Julio Eduardo Arce (Trees, Forests and People, 2022)
The Araucaria Forest is one of the most threatened ecosystems in Brazil due to selective logging and deforestation, mainly during the 20th century. The great majority of remnants are secondary forests with less than 50 ha, i.e., old-growth fragments are extremely rare. By presenting the characterization of rare old-growth fragments in comparison with secondary ones, the present study delivers unprecedented results about their composition, structure, and dendrometric characterization. In total, 22 clusters were installed: 12 clusters (37 plot units, 37,000 m²) in old-growth forest and 10 clusters (38 plot units, 38,000 m²) in secondary forest. Analyses included a dendrometric characterization (N, d, ddom, h, hdom, G and V), a phytosociological classification and multivariate analysis. Results indicated that old-growth and secondary forests show relevant differences at both dendrometric and phytosociological levels. The volume of old-growth forests, 582 m3 ha−1 (362–893 m3 ha−1), is substantially higher than that observed for secondary ones, 334 m3 ha−1 (193–501 m3 ha−1). A. angustifolia accounts for 55% (6–90%) of the volume in the old-growth forests, yet only 21% (0–52%) in the secondary. Multivariate analysis showed that old-growth forests are positively correlated with d, h, and G but negatively correlated with S and the Shannon index.